HUBUNGAN KADAR NATRIUM DAN KALIUM SERUM DENGAN TEKANAN DARAH DAN DENYUT NADI PADA PASIEN GAGAL JANTUNG - Asworo, Fadhillah Noor Izza; Hediningsih, Yekti; Marfuati, Nanik (Mandala Of Health, 2024)
Heart failure is the inability of the heart to carry out its function, namely pumping blood at a normal frequency for tissue needs, which causes compensatory mechanisms, namely activation of the renin-angiotensin system, narrowing of the arteries and release of adrenergic. The renin-angiotensin system will increase renin which will then increase aldosterone, causing changes in serum sodium levels and serum potassium levels. Meanwhile, narrowing of the arteries due to decreased contractility will affect blood pressure, while adrenergic release will increase the pulse rate. This study aims to prove the relationship between serum sodium and potassium levels with blood pressure and pulse rate in heart failure patients. This research is a cross sectional study, with 23 patients as respondents. Samples were collected using the sequential sampling method. The data used are medical records that check serum sodium and potassium levels at one time with blood pressure and pulse. The results obtained showed that the average serum sodium level was 135.7 ± 6.643 mEq/L, the average serum potassium level was 4,087 ± 0.7485 mEq/L, the average systolic blood pressure was 123.35 ± 29.518 mmHg, the average mean diastolic blood pressure 70.43 ± 31,334 mmHg, mean pulse 99 ± 31,010 times per minute. The significance value of the Spearman Rank test on serum sodium levels with blood pressure was 0.910 (p>0.05), on sodium levels with pulse rate was 0.713 (p>0.05), on serum potassium levels with blood pressure was 0.076 (p> 0.05), and serum potassium level with pulse was 0.344 (p>0.05). It can be concluded that there is no significant relationship between serum sodium and potassium levels and blood pressure and pulse rate.